Kebangkitan Ekonomi Rusia Pasca-Uni Soviet: Studi Kasus Reformasi Kepemimpinan Putin - Subiantoro, Yudi; Manurung, Hendra; Pannyiwi, Rahmat (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
The collapse of the Soviet Union in 1991, followed by the transition to an open market economy in Russia presented various economic and political dynamics. Boris Yeltsin's leadership was, in fact, unable to solve the fundamental problems related to domestic political and economic developments, and therefore Putin's firm leadership, consistent attitudes, and centralistic decision-making began to bring Russia's progress toward a Great Power in the early 2000s. This paper aims to analytically describe the revival of the Russian economy after the collapse of the Soviet Union through Putin's leadership. Putin-era economic reforms aimed to restore national political stability and economic growth with policies of simplifying the tax system, nationalizing natural resources and optimal utilization, and reducing dependence on foreign loans. These reforms succeeded in increasing gross domestic product (GDP) growth, reducing poverty and unemployment, and attracting foreign investment. However, criticism of reliance on energy exports, corruption, and the impact of international sanctions are still systemic problems in Russia. The qualitative case study approach method is used to analyse Putin-era economic reforms and their impact on Russian economic growth. Content analysis and economic data suitability are used as data processing methods. This study contributes to the academic debate on the effectiveness of various economic development models and the state's role in the absorption of the market economy. This paper has a significant impact on efforts to maintain the balance of global and regional economic power so that it can be a reference for policymakers, investors, and international economic analysts to understand the trends and prospects of the Russian economy in the future. It is concluded that Russian leadership of President Vladimir Putin served from early 2000 to 2008 and from 2012 to 2024, then slowly began to advance his country again and slowly rose to reclaim the status of great power in the world political arena, challenging the hegemony of the West which is increasingly dominating in the international system.